COUNSELING MODEL BASED ON GUSJIGANG CULTURE: CONCEPTUAL FRAMEWORK OF COUNSELING MODEL BASED ON LOCAL WISDOMS IN KUDUS - Zamroni, Edris (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
This article discusses the developing of conceptual framework of gusjigang counseling model as a manifestation of local wisdoms hold by the people of Kudus regency. Gusjigang is a philosophy of life taught by Sunan Kudus (one of the nine Java island’s first Muslim missionaries) which teaches men to have a good behavior (gus), to be good at reciting Koran (ji) as well as trading (gang). Gusjigang counseling model is close to Islamic counseling nuance which sets out the Islamic values of Kudus people who have been widely known as religious people. The goals of this counseling model are to develop men's virtuous characters, scientific and systematic thoughts, and improve persistence, creativity, innovativeness to survive.